Efficacy of avalglucosidase alfa on forced vital capacity percent predicted in treatment-naïve patients with late-onset Pompe disease: A pooled analysis of clinical trials - Tahseen Mozaffar; Lionel Riou França; Jérôme Msihid; Pragya Shukla; Irina Proskorovsky; Tianyue Zhou; Magali Periquet; Kristina An Haack; Laurence Pollissard; Volker Straub (Molecular Genetics and Metabolism Reports, 2024)
Background: The efficacy of avalglucosidase alfa (AVA) versus alglucosidase alfa (ALG) on forced vital capacity percent predicted (FVCpp) in patients with late-onset Pompe disease (LOPD) has been assessed in the Phase 3 COMET trial (NCT02782741). Due to the rarity of LOPD and thus small sample size in COMET, additional data were analyzed to gain further insights into the efficacy of AVA versus ALG. Methods: Data from treatment-naive patients with LOPD were pooled from COMET and Phase 1/2 NEO1/NEO-EXT (NCT01898364/NCT02032524) trials for patients treated with AVA, and Phase 3 LOTS trial (NCT00158600) for patients treated with ALG. Regression analyses using mixed models with repeated measures consistent with those pre-specified in COMET were performed post-hoc. Analyses were adjusted for trials and differences in baseline characteristics. Four models were developed: Model 1 considered all trials; Model 2 included Phase 3 trials; Model 3 included Phase 3 trials and was adjusted for baseline ventilation use; Model 4 included COMET and NEO1/NEO-EXT (i.e., AVA trials only). Results: Overall, 100 randomized patients from COMET (AVA, n = 51, ALG, n = 49), 60 from LOTS (ALG arm only), and three patients from NEO1/NEO-EXT (who received open-label AVA only) were considered for analysis. Mean age at enrollment was similar across trials (45.3–50.3 years); however, patients from LOTS had a longer mean duration of disease versus COMET and NEO1/NEO-EXT trials (9.0 years and 0.5–2.2 years, respectively) and younger mean age at diagnosis (36.2 years and 44.7–48.6 years, respectively). Least squares mean (95% confidence interval) improvement from baseline in FVCpp at Week 49–52 for AVA versus ALG was 2.43 (−0.13; 4.99) for COMET (n = 98); 2.31 (0.06; 4.57) for Model 1 (n = 160); 2.43 (0.21; 4.65) for Model 2 (n = 157); 2.80 (0.54; 5.05) for Model 3 (n = 154); and 2.27 (−0.30; 4.45) for Model 4 (n = 101). Conclusions: Models 1 to 3, which had an increased sample size versus COMET, demonstrated a nominally significant effect on FVCpp favoring AVA versus ALG after 1 year of treatment, consistent with results from COMET.